Identification of a major QTL, Parth6.1 associated with parthenocarpic fruit development in slicing cucumber genotype, Pusa Parthenocarpic Cucumber-6 - Devi, Shilpa; Sharma, Parva Kumar; Behera, Tusar Kanti; Jaiswal, Sarika; Boopalakrishnan, G.; Kumari, Khushboo; Mandal, Neha Kumari; Iquebal, Mir Asif; Gopala Krishnan, S.; Bharti,; Ghosal, Chandrika; Munshi, Anilabha Das; et al. (Frontiers in Plant Science, 2022)
Parthenocarpy is an extremely important trait that revolutionized the worldwide cultivation of cucumber under protected conditions. Pusa Parthenocarpic Cucumber-6 (PPC-6) is one of the important commercially cultivated varieties under protected conditions in India. Understanding the genetics of parthenocarpy, molecular mapping and the development of molecular markers closely associated with the trait will facilitate the introgression of parthenocarpic traits into non-conventional germplasm and elite varieties. The F1, F2 and back-crosses progenies with a non-parthenocarpic genotype, Pusa Uday indicated a single incomplete dominant gene controlling parthenocarpy in PPC-6. QTL-seq comprising of the early parthenocarpy and non-parthenocarpic bulks along with the parental lines identified two major genomic regions, one each in chromosome 3 and chromosome 6 spanning over a region of 2.7 Mb and 7.8 Mb, respectively. Conventional mapping using F2:3 population also identified two QTLs, Parth6.1 and Parth6.2 in chromosome 6 which indicated the presence of a major effect QTL in chromosome 6 determining parthenocarpy in PPC-6. The flanking markers, SSR01148 and SSR 01012 for Parth6.1 locus and SSR10476 and SSR 19174 for Parth6.2 locus were identified and can be used for introgression of parthenocarpy through the marker-assisted back-crossing programme. Functional annotation of the QTL-region identified two major genes, Csa_6G396640 and Csa_6G405890 designated as probable indole-3-pyruvate monooxygenase YUCCA11 and Auxin response factor 16, respectively associated with auxin biosynthesis as potential candidate genes. Csa_6G396640 showed only one insertion at position 2179 in the non-parthenocarpic parent. In the case of Csa_6G405890, more variations were observed between the two parents in the form of SNPs and InDels. The study provides insight about genomic regions, closely associated markers and possible candidate genes associated with parthenocarpy in PPC-6 which will be instrumental for functional genomics study and better understanding of parthenocarpy in cucumber.